Trace elements: chrome, cobalt and nickel in patients with psoriasis vulgaris in different development phases Part I. Concentration of chrome, cobalt and nickel in selected morphotic components and excreta - Stępień, Beata; Seneczko, Franciszek; Seneczko, Michał; Kijawski, Robert (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2004)
There was taken the comparative examination of chrome, cobalt and nickel concentration in red blood cells, plasma, urine, hair and nails in 31 healthy persons (11 females and 20 males) and 31 persons suffering from psoriasis vulgaris (10 females and 21 males). It has been confirmed that the concentration of chrome and cobalt, and to a less degree of nickel, in red blood cells and plasma are reduced, what may have conections with different part of psoriasis pathogenesis. The concentration of chrome, cobalt and nickel in urine, nail plate and hair shaft does not indicate significant differences among healthy persons and psoriasis patients.